FAKTOR GAYA HIDUP DAN STRES YANG BERISIKO TERHADAP KEJADIAN PENYAKIT JANTUNG KORONER PADA PASIEN RAWAT JALAN - Yadi, Ahmad; Hernawan, Andry Dwi; Ridha, Abduh (Fakultas Ilmu Kesehatan Universitas Muhammadiyah Pontianak, 2014)
Coronary Heart Disease (CHD) began because of the presence of atherosclerosis in the coronary arteries resulting in inhibition of blood flow to the heart muscle. CHD event rates in RSUD Dr. Soedarso Pontianak each year has increased. In 2010 the proportion of CHD of Â 2.99%, an increase in 2011 amounted to 3.38%, and in 2012 amounted to 3.27%. This study aims to determine the risk factors for CHD in Outpatients Heart Clinic RSUD Dr. Sodarso Pontianak. This study uses a case-control design. Study sample, 72 respondents (36 cases and 36 controls) were taken using purposive sampling technique. Using the Chi-square test with a confidence level of 95%. The results showed there is a significant relationship between physical activity Â (p value = 0.001; OR = 6.250, 95% CI = 2.090 to 18.695), the consumption of fried food = 2 times a week (p value = 0.009; OR = 4.02, 95% CI = 1.50 to 10.74), and smoking habits (p value = 0.034; OR = 3.14, 95% CI = 1.19 to 8.24). It is recommended to RSUD Dr. Soedarso Pontianak to establish a health promotion clinic, utilizing the waiting room and open space for education, healthy campaign activities, as well as socialization and supervision No Smoking Area and provide sanctions for violations No Smoking Area hospital.